Answer:
Supply equation is p=(22/7000)*q+3
The demand equation is p=-(45/7000)*q+70
Explanation:
Let supply equation be P=aq+b
Let demand equation be P=cq+d
P=price per unit while q=quantity manufactured and sold
According to the information given the producer will produce zero unit at the price of $3
In other words,when p=$1,q=0
3=a(0)+b
b=3
At equilibrium q=7000 units and p=$25
Therefore,25=7000a+3
25-3=7000a
22=7000a
a=22/7000
Supply equation is p=(22/7000)*q+3
According to data given consumers will demand zero unit at the price of $70
p=$70 when q =0
Supply equation is given as
p=2
P=cq+d
70=c(0)+d
d=70
at equilibrium q=7000,p=25
25=7000c+70
25-70=7000c
-45=7000c
c=-45/7000
Demand equation is given as :
p=-(45/7000)*q+70